(untitled) (World Economics and Finance Bulletin, 2024)
The research aims to uncover the relationship between strategic planning through its dimensions (Formulating the strategic mission and vision, setting strategic goals, analyzing the external environment, analyzing the internal environment, determining factors affecting the success of the strategic choice) and improving human resources performance. The research problem was identified in the main question, which is what is the nature of the relationship between the research variables, and for that purpose a main research plan hypothesis was formulated and a subsidiary one that emerged from it, and in order to determine the validity of the hypotheses, the hypotheses were subjected to multiple tests to verify their validity. The research used the questionnaire as a means to obtain dat. The research community (104) faculty and staff in the Administrative Technical College / Kufa, and the research applied the random sample to select (66) performance and employees, where the sample represented (63%) of the total research community. The research used the questionnaire as a means or tool to obtain data. A set of statistical methods and techniques were used in the data analysis process, and the results were extracted according to the statistical package program (SPSS v.22). The research reached a set of conclusions, the most important of which was the need for the senior leadership in the college to have a clear vision and work to consolidate the culture of employee participation in strategic planning and the decision-making process in everything related to the college, as well as work to diagnose problems facing the organizational work environment and develop appropriate solutions to them through Flexibility in dealing with workers at the organizational level as a whole, which in turn represents the most important strategic, organizational and environmental factors that contribute to improving human resource performance.